Outsourcing Public Services: Contractibility, Cost, and Quality - Fredrik Andersson; Henrik Jordahl; Jens Josephson (Örebro University School of Business, 2019)
We review the literature on public sector outsourcing to explore if the theoretical predictions from the incomplete contracts literature hold up to recent empirical evidence. Guided by theory, we arrange services according to the type and magnitude of their contractibility problems. The empirical studies point at rather favourable outsourcing outcomes, in terms of costs and quality, for services without severe contracting problems. The picture is more mixed for services with tougher contracting problems, with the weight of the evidence in favour of public provision. This difference between services is largely in line with the property-rights framework and theories of incomplete contracts.
Keywords: D23; H11; L33; 330; privatization; property rights; publicly provided goods